2016
DOI: 10.1111/jam.13226
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic activity of Enterococcus faecalis CECT7121: effects on mucosal immunity and intestinal epithelial cells

Abstract: Our results indicate that, apart from its already reported systemic immune activity, Ent. faecalis CECT7121 has a modulatory effect at a local level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…For instance, Er et al (2015) studied the cytotoxicity of three LAB ( Pediococcus pentosaceus, Lactobacillus plantarum , and Weissella confusa ) on Caco-2 cells and showed dose-dependent cytotoxic effects of the cell-free filtrates and cell-free lyophilized filtrates of the three LAB. Similarly, a recent work performed by Castro et al (2016) demonstrated that E. faecalis CECT7121 strain is not cytotoxic for Caco-2 cells.…”
Section: Resultsmentioning
confidence: 63%
“…For instance, Er et al (2015) studied the cytotoxicity of three LAB ( Pediococcus pentosaceus, Lactobacillus plantarum , and Weissella confusa ) on Caco-2 cells and showed dose-dependent cytotoxic effects of the cell-free filtrates and cell-free lyophilized filtrates of the three LAB. Similarly, a recent work performed by Castro et al (2016) demonstrated that E. faecalis CECT7121 strain is not cytotoxic for Caco-2 cells.…”
Section: Resultsmentioning
confidence: 63%
“…Fifty-eight LAB strains belonging to 6 species usually involved in cheese production as starter or adjunct cultures were evaluated for their cholesterol-lowering potential. Data related to the in vitro tests highlighted a broad diversity in the hypocholesterolemic action at both species and strain levels, confirming that each probiotic strain within each species may have different activities (Castro et al, 2016). In contrast with Pan and Zhang (2005), who found a Lc.…”
Section: Discussionmentioning
confidence: 79%
“…One way to improve the diversity and composition of gut microbial communities is to supplement the diet with probiotics [ 13 ]. Probiotics are viable bacteria that maintain gut health through the production of organic acids [ 24 ], prime the immune system [ 25 , 26 ] and help in the saturation of enterocytes [ 27 ] for pathogen colonisation resistance. Bacteria such as Lactobacillus , Bacillus , Bifidobacterium and Streptococcus are used for probiotics formulation that are commercially available for poultry industry.…”
Section: Introductionmentioning
confidence: 99%